2007
DOI: 10.1111/j.1462-5822.2007.00924.x
|View full text |Cite
|
Sign up to set email alerts
|

A bacterial ecto-triphosphate diphosphohydrolase similar to human CD39 is essential for intracellular multiplication of Legionella pneumophila

Abstract: As part of its pathogenesis, Legionella pneumophila persists within human alveolar macrophages in non-acidified organelles that do not mature into phagolysosomes. Two L. pneumophila genes, lpg0971 and lpg1905, are predicted to encode ecto-nucleoside triphosphate diphosphohydrolases (ecto-NTPDases) that share sequence similarity with human CD39/NTPDase1. The predicted products possess five apyrase conserved domains that are typical of eukaryotic ecto-NTPDases. In this study, we found that an lpg1905 mutant was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
91
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 61 publications
2
91
0
1
Order By: Relevance
“…Indeed, some of these proteins have meanwhile been shown to be implicated in host pathogen interactions Sansom et al 2007). As regards the eukaryotic-like genes de Felipe et al 2005;Brüggemann et al 2006a) our analysis revealed that they are present only in L. pneumophila strains and are absent or far less conserved in non-pneumophila strains.…”
Section: Phylogenetic Lineages Do Not Correlate With Geographical or mentioning
confidence: 82%
“…Indeed, some of these proteins have meanwhile been shown to be implicated in host pathogen interactions Sansom et al 2007). As regards the eukaryotic-like genes de Felipe et al 2005;Brüggemann et al 2006a) our analysis revealed that they are present only in L. pneumophila strains and are absent or far less conserved in non-pneumophila strains.…”
Section: Phylogenetic Lineages Do Not Correlate With Geographical or mentioning
confidence: 82%
“…Interestingly, the apyrase conserved regions corresponding to the active domain of NTPDase are almost ubiquitous in eukaryotes and absent in prokaryotes except Legionella pneumophila (15,16). In contrast, eNs are widespread in bacteria, but only a few of them have been characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, functional homologues of CD39 have been identified in a number of microbial human pathogens (14), such as Legionella pneumophila (15)(16)(17), and proteins belonging to the CD73 family of ecto-5Ј-nucleotidase have been identified in Staphylococcus aureus, Bacillus anthracis, and Streptococcus sanguinis (18 -21). Inactivation of these bacterial ectonucleotidases impairs virulence but not viability, suggesting that their selective inhibition might be a new therapeutic strategy.…”
mentioning
confidence: 99%
“…Numerous interactions may occur between mitochondria, AMPK and L. pneumophila virulence factors during pathogenesis. For example, it was reported recently that one of the secreted virulence factors produced by L. pneumophila, Lpg1905, is a novel ecto-nucleoside triphosphate diphosphohydrolase (ecto-NTPDase or apyrase) (Sansom et al, 2007). Lpg1905 exhibited ATPase and ADPase activity and contributed to the ability of L. pneumophila to infect and replicate in macrophages, epithelial cells and amoebae.…”
Section: Dmmbiologistsorg 484mentioning
confidence: 99%
“…Lpg1905 exhibited ATPase and ADPase activity and contributed to the ability of L. pneumophila to infect and replicate in macrophages, epithelial cells and amoebae. Lpg1905 may act as a virulence factor by regulating extracellular or intracellular levels of ATP, depending on whether secretion occurs before or after Legionella uptake by the host cell (Sansom et al, 2007;Sansom et al, 2008). An intracellular site of action seems probable if apyrase secretion accompanies that of other virulence factors that are known to be secreted within the host cell after pathogen uptake.…”
Section: Dmmbiologistsorg 484mentioning
confidence: 99%